STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA BERDASARKAN IMPLEMENTASI Permen PANRB NOMOR 1 TAHUN 2023 TENTANG JABATAN FUNGSIONAL PADA BAGIAN PROTOKOL DAN KOMUNIKASI PIMPINAN KOTA - Dwi Sofian, Octa (STIA MALANG, 2024)
This research aims to determine human resource development strategies based on the implementation of PANRB Ministerial Regulation Number 1 of 2023 concerning Functional Positions in the Protocol and Communication Section of Batu City Leadership. The problem is focused on development strategies in the form of training, education and coaching. This research refers to the implementation of functional position competency development as stated in competency development in Article 46 of PANRB Ministerial Regulation Number 1 of 2023. The research method used is descriptive qualitative by analyzing human resource development strategies. Data was collected through interviews with department heads. and staff in the Leadership Protocol and Communications Section. This study concludes that the implementation of the development strategy has been implemented and improvements are needed at certain points during activities.